2023
DOI: 10.1021/acsnano.3c04569
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline Cellulose Modulates Dysregulated Intestinal Barriers in Ulcerative Colitis

Mingzheng Wang,
Ruitao Cha,
Wenshuai Hao
et al.

Abstract: Ulcerative colitis (UC) is a recurrent chronic inflammation of the colon with increasing incidence and prevalence, which could increase the risk of colorectal cancer. It is urgent to find an effective method with few side effects. Nanocrystalline cellulose (NCC), which is from plant fibers, has a good biocompatibility and high biosafety. Herein, we used NCC to treat UC and evaluated its treatment effect by the disease activity index, intestinal pathology, inflammatory cytokines, tight junction proteins, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Besides mucus, tight junction protein between intestinal epithelial cells, as a mechanical barrier of colon, is an important aspect of defending dangerous compounds in colon cavity . Reduction of the tight junction protein is another most notable feature in the course of IBD development.…”
Section: Resultsmentioning
confidence: 99%
“…Besides mucus, tight junction protein between intestinal epithelial cells, as a mechanical barrier of colon, is an important aspect of defending dangerous compounds in colon cavity . Reduction of the tight junction protein is another most notable feature in the course of IBD development.…”
Section: Resultsmentioning
confidence: 99%
“…cerana. , Our study also suggests that L. apis participates in the antiviral response and that JNCC regulates the dysfunctional gut microbiota in bees after viral infection. Similarly, plant NCC was found to modulate dysregulated intestinal barriers in ulcerative colitis and cure constipation via gut microbiota. , Although there has not been any direct evidence of antiviral function in insects, numerous reports have confirmed that Lactobacillus plays a crucial role against viral infection in vertebrates. , …”
Section: Resultsmentioning
confidence: 99%